2008
DOI: 10.1002/pros.20852
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor expression by human prostate cancers

Abstract: BACKGROUND Although recent laboratory and population studies suggest that prostate cancer may be responsive to insulin, there is a gap in knowledge concerning the expression of insulin receptors on benign or malignant prostate tissue. METHODS We immunostained 644 cores on tissue microarrays prepared from 29 prostate tissue samples without malignancies, 78 Gleason grade 3 cancers, 21 Gleason grade 4 cancers and 33 Gleason grade 5 cancers with antibodies against the insulin‐like growth factor I receptor and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
129
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(137 citation statements)
references
References 45 publications
7
129
0
1
Order By: Relevance
“…In addition, the results from these analyses often failed to be consistent. IGF1R levels were reported to be down-regulated, 14 up-regulated, 15,16 or not changed 17,18 in local prostate cancer. The IGF1R is a tyrosine kinase receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results from these analyses often failed to be consistent. IGF1R levels were reported to be down-regulated, 14 up-regulated, 15,16 or not changed 17,18 in local prostate cancer. The IGF1R is a tyrosine kinase receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported were often inconsistent. For example, IGF1R levels were reported to be down-regulated, 14 up-regulated, 15,16 or not changed 17,18 in local prostate cancer. Clinical trials investigating the therapeutic efficacy of an anti-IGF1R therapy in prostate cancer are registered in the US National Institutes of Health database of clinical studies (http://www.clinicaltrials.gov).…”
mentioning
confidence: 99%
“…In general, obese men have higher insulin levels than normal weight men, 16 and prostate cancers have recently been shown to express the insulin receptor at high levels. 17 Moreover, in multiple studies higher insulin levels among men with prostate cancer have been linked with prostate cancer death. 18,19 In addition, obese men have lower androgen levels, which may promote more aggressive cancers, 20 though this remains a controversial hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is composed of an IR hemi-receptor linked to an IGF-IR hemi-receptor and has been reported to have an important role in cancer biology (29)(30)(31). Recently, the two IR isoforms (IR-A and IR-B) have been reported that are overexpressed in cancer tissues (32), whereas the expression of IGF-1R has been previously characterized in KLE cells in our laboratory (7). Therefore, aiming to the characterize the MGF E-peptide actions in KLE cells, we performed a series of silencing experiments of these major receptors involved in the IGFmediated actions.…”
Section: Discussionmentioning
confidence: 99%